An Investigation into Organisation Capacity for National Disaster Management in Zimbabwe: The Case of the Department of Civil Protection - Mutizwa, Bismark (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Across the globe, disasters – both natural and man-made – have threatened humanity. These disasters had grave and devastating impact on human life, infrastructure, and the environment as evidenced by the February 2000 Cyclone Eline and March 2019 Cyclone Idai. This research sought to investigate the Department of Civil Protection`s (DCP) capacity in national disaster management. The research examines how the DCP handled cyclones from 2000-2019 in Chimanimani District. Organisational capacity was assessed on the basis of its core principles which are: leadership, management and operations, community engagement, service and evaluation. The study discovered that inadequate financial and human resources, poor emergency response systems, weak learning and lessons drawing, reactive disaster management, weak pre-disaster management community engagement, poor reconstruction and failure to harmonise military and DCP operational structures are factors undermining DCP`s capacity for national disaster management. The research recommends that government should avail adequate resources, DCP should be proactive in disaster management, should openly contract-out reconstruction works, and collaborate with universities to strengthen organisational learning capacity, align military and DCP operational structures and processes and let Non-Governmental Organisations (NGO) distribute food and other humanitarian aid.